Gravitating towards technology-based emerging financial crime: A PRISMA-based systematic review - Ghose, Provakar; Parvin, Munira; Akter, Sadia; Rakib, Shakib Hassan; Bhuiyan, Mohammad Rakibul Islam (International Journal of Innovative Research and Scientific Studies, 2025)
This study explores the integration of emerging technologies into financial systems and their impact on financial crimes. The research aims to identify and categorize financial crimes, cyber breaches, and the role of digital evidence in financial technologies using the PRISMA technique. A systematic review was conducted, analyzing literature from multiple databases such as PubMed, Scopus, Web of Science, and Google Scholar, focusing on studies published between June 2021 and June 2023. Key terms, including "technology-based financial crime," "cybercrime," "financial fraud," and others, were incorporated to refine the search. After rigorous screening, 175 studies (150 papers and 25 reports) were selected for analysis. The study highlights the growing concern over the use of emerging technologies in facilitating financial crimes such as money laundering, tax evasion, and cyber fraud. It also examines the evolving nature of financial crimes due to technological advancements and the challenges of investigating and prosecuting such crimes. Further research is recommended to investigate the socio-economic factors influencing financial crime and to develop effective global collaboration mechanisms for addressing transnational financial offenses. This study contributes to a deeper understanding of how business entities and individuals handle financial misconduct in the digital era.